Severe Short Stature in an Adolescent Male with Prader-Willi Syndrome and Congenital Adrenal Hyperplasia: A Therapeutic Conundrum - Meredith Wasserman; Erin M. Mulvihill; Angela Ganan-Soto; Serife Uysal; Jose Bernardo Quintos (Case Reports in Endocrinology)
Congenital adrenal hyperplasia (CAH) due to 21-hydroxylase deficiency results in excess androgen production which can lead to early epiphyseal fusion and short stature. Prader-Willi syndrome (PWS) is a genetic disorder resulting from a defect on chromosome 15 due to paternal deletion, maternal uniparental disomy, or imprinting defect. Ninety percent of patients with PWS have short stature. In this article we report a patient with simple-virilizing CAH and PWS who was overtreated with glucocorticoids for CAH and not supplemented with growth hormone for PWS, resulting in a significantly short adult height.